Isolation and identification of some bacterial isolates from soil contaminated with crude oil and Testing Their Effectiveness (Baghdad Science Journal, 2021)
Bacterial strains were isolated from oil-contaminated soil, in 2018, these isolates were identified, and with the aim of finding out the ability of these isolates to degrede the oil compounds, the color change of medium which added to it isolates was read by the method of Pacto Bushnell Hans. Then the change in the petroleum compounds was read by gas chromatography, for the most effective isolates.The nine isolated bacterial showed different degrees of color change, and the isolates (Pseudomonas, Bacillus, Micrococcus) outperformed the color change amount (78, 78, 77) %, respectively, compared to the control, and the three isolates together showed the best color change of 90.7. % Compared to the control, and the results of separating materials by means of gas chromatography showed that there were changes in the nature of the materials present in the crude oil (control: without isolates) compared to those present in the crude oil That disintegrated by means of the three single isolates. The three isolates together showed a greater ability to change the nature of the materials present in the crude oil. Which confirms the effectiveness of each isolate separately and the ability of these isolates together to degerde crude oil.